Analisis Qos Dengan Metode Traffik Shaping Pada Jaringan Internet (Study Khasus : PT. Netciti Persada Alam Sutera - Tangerang) - Bambang Suteja Bambang; Niki Ratama (Journal of Research and Publication Innovation, 2023)
Network analysis using QOS (quality of service) in particular is latency and throughput capable of providing good network analysis, where these aspects are often used in network analysis. QOS (quality of service) is defined as one of the mechanisms or ways that enable services to operate according to their respective characteristics in an IP (Internet Protocol) network. QOS (quality of service) refers to the ability of a network to provide better service to a given network traffic through different technologies. QOS (quality of service) offers the ability to define the attributes of network services provided, both qualitatively and quantitatively. There are 4 parameters in measuring QOS (quality of service), namely packet loss, delay, jitter, and throughput. While Traffick Shaping is a network that connects between computers and provides access to various network application services such as computer data services. In multi-service computer networks or the internet, problems often arise, where certain services can consume large amounts of bandwidth which causes other services to be unable to get the required bandwidth. For this reason, it is necessary to monitor the use of bandwidth in an application service in the network by dividing the bandwidth for each service according to the needs, so that each service can be used optimally in a network according to the bandwidth allocation that has been arranged or determined.